A novel chemical reduction/co-precipitation method to prepare sulfur functionalized reduced graphene oxide for lithium-sulfur batteries. (1st June 2020) - Wadekar, Pravin H.; Ghosh, Arnab; Khose, Rahul V.; Pethsangave, Dattatray A.; Mitra, Sagar; Some, Surajit
Abstract: The higher theoretical specific capacity with considerable cell potential, Lithium–Sulfur batteries (LSBs) are considered to be high-energy storage strategies near future. However, the practical realization of LSBs is being hindered owing to low cell capacity risen from poor electronic-conductivity of elemental sulfur. To enhance the electronic-conductivity and thus to improve the specific cell capacity, commonly conducting carbons such as reduced graphene oxide, carbon nanotubes etc. are used as additives in the electrodes. Here, we report a unique in-situ synthesis strategy to prepare a composite of sulfur-functionalized reduced graphene oxide (SFRGO) encapsulating monodisperse sulfur nanoparticles using a low-cost deep eutectic solvent (DES) derived from choline chloride and sodium thiosulfate. The DES serves as an effective reductant as well as dopant. Moreover, during formation of SFRGO, a major fraction of the DES degrades to elemental sulfur. The SFRGO composite has been applied as cathode material in LSBs. The cathode material delivered a maximum specific capacity of 1265 mA h g −1 during initial cycle and retains 903 mA h g −1 after 100 cycles, with a usual capacity decay rate 0.28% each cycle. This facile chemical reduction method is an alternative to the large-scale and cost-effective production of high-quality graphene for energy storage application. Graphical abstract: Herein, we have developed choline chloride-based novel deep eutectic solvent for the reduction of graphene oxide subsequently the preparation of sulfur functionalized graphene for their application in Lithium–Sulfur batteries. Image 1